FIRST-GENERATION F1 HYBRID TOMATO VARIETIES FOR OPEN FIELD CULTIVATION IN SOUTHERN UZBEKISTAN, RESISTANT TO ROOT-KNOT NEMATODES, AND SUITABLE FOR EXPORT - P.N. Khojayev,; J.N. Nadjiev, (The Bioscan, 2024)
The article presents the results of the study of new F1 hybrids of tomatoes selected by the Surkhandarya Research and Experimental Station in 2020-2021, high-yielding, transportable and resistant to root-knot nematode, as a result, F1Namuna x L-46 hybrids with high total yield and F1Dystlik x L-46 hybrids with the highest heterosis effect in total and early yield were isolated. In addition, the hybrids F1 On the Moon Shackle, F1 Namuna x L-59 and F1Dystlik x L-46 are considered resistant to the root-knot nematode.